Financial stability in Indonesian Islamic banking using Z-Score: Before and during Covid-19 - Moh Alfiyan; Rofiul Wahyudi; Maimunah Binti Ali Maimunah; Riduwan Riduwan (Universitas Negeri Surabaya, 2023)
This study aims to analyze the level of comparison of the financial stability of Islamic banking in the period before and during the Covid-19 pandemic. This study uses a paired T-test by taking samples of 13 Islamic Commercial Banks that publish financial reports regularly on the website of OJK in quarter I 2019 – quarter IV 2020. The results explain that Z-Score, BOPO, NPF, HHI, GDP and Inflation have no differences in the average level before pandemic compared to during the Covid-19 pandemic. Then FDR, Bank Size and BI Rate have differences in the average level before pandemic compared to during the Covid-19 pandemic. The results of the comparative analysis of the financial stability of Islamic banking before the Covid-19 pandemic compared to during the Covid-19 pandemic through the Z-Score analytical explained that Islamic banks were more stable before the pandemic, but still had good stability during the Covid-19 pandemic.